2018
DOI: 10.3389/fpsyg.2018.01883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ability and Effort Praise on Children’s Failure Attribution, Self-Handicapping, and Performance

Abstract: Previous research has suggested that children praised for ability are more likely to attribute their failure to low ability compared to those who are praised for effort. At the same time, self-worth theory suggests that when an individual’s self-worth is threatened, they are likely to use a self-serving attributional strategy and self-handicapping. From the perspective of self-worth theory, the present study investigated how ability and effort praise influenced children’s failure attribution, self-handicapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(71 reference statements)
1
14
0
4
Order By: Relevance
“…Our findings concur with a broader line of research on how messages that focus on the process (e.g., effort, strategies) underlying performance may benefit children’s achievement. For example, research has shown that when children are praised for their effort on a task, this may help them bounce back from setbacks (Mueller & Dweck, 1998; Xing, Gao, Jiang, Archer, & Liu, 2018), and that teaching parents to deliver more effort praise benefits children’s reading and writing achievement over time (Andersen & Nielsen, 2016). Interestingly, there is some evidence that the benefits of such a process focus may be especially pronounced for students with negative competence beliefs (Pomerantz et al, 2006)—consistent with our finding that effort self‐talk benefits those with negative competence beliefs, who, without intervention, performed worse than others.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings concur with a broader line of research on how messages that focus on the process (e.g., effort, strategies) underlying performance may benefit children’s achievement. For example, research has shown that when children are praised for their effort on a task, this may help them bounce back from setbacks (Mueller & Dweck, 1998; Xing, Gao, Jiang, Archer, & Liu, 2018), and that teaching parents to deliver more effort praise benefits children’s reading and writing achievement over time (Andersen & Nielsen, 2016). Interestingly, there is some evidence that the benefits of such a process focus may be especially pronounced for students with negative competence beliefs (Pomerantz et al, 2006)—consistent with our finding that effort self‐talk benefits those with negative competence beliefs, who, without intervention, performed worse than others.…”
Section: Discussionmentioning
confidence: 99%
“…De esta forma, la identificación de las variables que, dentro de cada perfil motivacional, tendrían una relación significativa con la utilización del self-handicapping y del pesimismo defensivo puede contribuir a determinar qué factores deben priorizarse de cara a prevenir o reducir la implicación de los estudiantes universitarios en estos mecanismos autoprotectores en función de sus características de autoestima y metas de logro. Asumiendo que tanto el self-handicapping como el pesimismo defensivo se asocian con importantes perjuicios personales y académicos a largo plazo (Lee et al, 2010;Norem & Cantor, 1990;Putwain, 2019;Schwinger et al, 2014;Xing et al, 2018), nuestros datos sugieren que las metas de aprendizaje, con independencia del nivel de autoestima del estudiante, podrían suponer un importante factor de protección frente al selfhandicapping. Por el contrario, el énfasis en el rendimiento situaría el foco en la comparación social (e.g., evitar la crítica), lo que se relacionaría con una tendencia más elevada a involucrarse en mecanismos de autoobstaculización, especialmente en estudiantes con alta autoestima.…”
Section: Implicaciones Educativasunclassified
“…Con independencia de su tipología, el impedimento le permite al estudiante generar una convincente coartada ante un previsible fracaso, de modo que, a ojos de los demás, la competencia personal quedaría eximida de toda sospecha (Berglas & Jones, 1978). El self-handicapping, así pues, resulta marcadamente eficaz en el corto plazo, por cuanto permite proteger los sentimientos de valía personal del estudiante (McCrea & Hirt, 2001), pero sus supuestos beneficios se diluyen a la larga, dado que la utilización recurrente de la estrategia a menudo comporta importantes perjuicios académicos (Cano et al, 2018;Schwinger et al, 2014) y emocionales (Putwain, 2019;Zuckerman & Tsai, 2005), especialmente acusados en el caso del selfhandicapping conductual (Xing et al, 2018).…”
Section: Introductionunclassified
“…Person praise refers to offering praise based on the personal qualities of a child, such as abilities (Brummelman et al, 2014 ). Although conventional wisdom supports the view that praising the traits of a child is beneficial for motivation (Kamins and Dweck, 1999 ), many researchers have argued that this may harm the motivation of an individual (Henderlong and Lepper, 2002 ; Henderlong Corpus and Lepper, 2007 ; Haimovitz and Corpus, 2011 ; Xing et al, 2018 ). For example, Mueller and Dweck ( 1998 ) discovered that if students are praised for abilities when they succeed in a task, their achievement motivation is reduced when they later fail (refer to also Kamins and Dweck, 1999 ; Skipper and Douglas, 2012 ).…”
Section: Introductionmentioning
confidence: 99%